Implementation of Barangay Disaster Risk Reduction Management in Barangay San Agustin Novaliches Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Philippines is one of the world's most susceptible countries when it comes to disasterssuch as typhoons, floods, landslides, volcanic eruptions, earthquakes, etc. The Philippinegovernment was able to come up with different adaptive strategies because of the pastdisasters that had already occurred. However, there are still gaps in disaster managementthat need to be filled in, especially given the limited quantity of data that is currently availableas a reference for local levels of preparedness. In this study, we dug deeper into theimplementation of barangay disaster risk reduction management in barangay San Augustin,Novaliches, and Quezon City.From the results of this study, it was revealed that the majority of the respondents "stronglyagree" that the implementation of barangay disaster risk reduction management in barangaySan Agustin, Novaliches, Quezon City was implemented in terms of communication andfacilities and that some of them "agree" to it in terms of emergency planning. It was alsoidentified that the barangay rarely conducts drills and seminars for its residents on what to dowhen a disaster occurs. They do not give early warning signals to their residents and basicallydo not have any emergency plans on hand.The results show the need for active dissemination of the early warning system, for it can helpincrease resilience by improving one's capacity to prepare ahead of time, which in turnincreases the barangay's and residents' abilities to quickly recover and decrease futurevulnerabilities. As attested by the overall respondents, the barangay should conduct regularsimulation exercises or drills to prepare for the identified primary hazards and risks fordisasters. Disasters can happen at any time of the day or in moments that we least expectthem to happen, so it is only befitting that the barangay takes care of its residents by equippingthem with enough knowledge to reduce or prevent any worst-case scenarios during a disaster.
Keywords: Criminology